Daily practice test: effects on mathematics performance in solving the fundamental operations on fractions - Alenton, Jun Carl (IJERI: International Journal of Educational Research and Innovation, 2022)
This experimental study evaluated the effects of implementing the Daily Practice test in solving fundamental operations on fractions as one of the deficiencies of students in Mathematics. Moreover, achievement test results reveal that one of the weaknesses of the students is mastery and computational fluency in solving problems involving fractions. The study aimed to compare daily testing and conventional review as a tool to master concepts involving fractions. This was made through the pre-posttest in the students’ performance before and after being exposed to daily testing. The respondents were grouped according to conventional review and a group exposed to the daily testing for eight weeks. Two distinct classes; experimental (n=75) and control (n=75) groups were randomly chosen. The results revealed that the students in both groups showed Below Average performance in the pretest but manifested a significant difference in the actual mean in the post-test. Both groups displayed significant improvement in solving fundamental operations on fractions. Further, the achievement of students under the Daily Practice Test showed Above Average performance and significantly helped in the improvement of students’ mastery in solving the fundamental operations on fractions. The paper concludes that daily testing has a positive impact on students’ mastery and have shown improvement in their study habits as tested often.